Chicken Feathers As An Alternative Substrate For Extracellular Keratinase Production Using Microsporum Fulvum Ibrl Sd3 By Solid Substrate Fermentation - Alyas, Nur Diyana (2013)
In nature, chicken feathers were abundantly generated from poultry industry and become severe environmental problems. The capabilities of microbial degradation and bioconversion of chicken feathers were directed to the reason for this study. The present study used the keratinaceous waste as a substrate in keratinase production from molecular identification of M. fulvum IBRL SD3 via solid substrate fermentation. The improvements of cultural conditions for maximal keratinase production in a shake flask system with particles size of substrate of 0.75 mm, at the initial moisture content of 100% (w/w), cultivation temperature of room temperature (30±2ºC), initial pH 7, mixing frequency at once every 24 hours and inoculum size of 1 X 107 spores/ml showed keratinase achieved 0.266 U/g of fermented substrate on day 6th of cultivation. In the improvement of medium compositions, no additional carbon source was required and a slight supplementation of 0.70% (w/w) of yeast extract to produce the maximum keratinase activity on day 6th of cultivation at 0.372 U/g of fermented substrate with the increment of keratinase activity at 905.41% compared to the initial profile. Furthermore, an improvement of tray system was conducted using a shallow aluminium tray (16 cm x 16 cm x 5 cm).